Toward New Media: Neutral, Creative, and Provide Solutions - Destiwati, Rita; Harahap, Junardi (SOSIOHUMANIKA, 2012)
ABSTRACT: Mass media can expand the horizons of thought and build sympathy, concentrating development goals so as to create a harmonious atmosphere, and effective development. The mass media has also the task social change in society, namely: (1) Expanding to horizon of view; (2) Focusing to public with messages written; (3) Rising the aspirations; and (4) Creating an atmosphere to build media. Mass media is often viewed as an effective instrument power for its ability to perform one or more several things such as: attracting and directing attention, persuade opinion and perception, affect the choice attitude, given the status and legitimacy, and define and shape reality perceptions. It is desirable once a mass media that serves as a counterweight, reformer, and herald of truth. This study tries to answer about the neutrality of the news stories related to socio-political issues. This study uses qualitative methods through a descriptive approach, observation, depth interviews, and literature study. The research results showed that the mass media about the social politics still less yet neutral. The results also showed that the news of media is still less yet neutral, exaggerating the problem, not provide solutions, and sometimes just give the sensation itself.KEY WORD: New media, news and views, communication, neutral, creative, provide solutions, and new changes.Â IKHTISAR: Media massa dapat memperluas cakrawala pemikiran dan membangun simpati, memusatkan tujuan pembangunan sehingga tercipta suasana yang harmonis, dan pembangunan yang efektif. Media massa juga memiliki tugas perubahan sosial di masyarakat, yaitu: (1) Memperluas Â cakrawala sudut pandang; (2) Fokus kepada public melalui pesan tertulis; (3) Meningkatkan aspirasi; dan (4) Menciptakan suasana dalam membangun media. Media massa sering dipandang sebagai kekuatan instrumen yang efektif karena kemampuannya dalam satu dan banyak hal untuk menarik dan mengarahkan perhatian, membujuk pendapat dan persepsi, mempengaruhi sikap pilihan, memberi status dan legitimasi, serta mendefinisikan dan membentuk persepsi realitas. Media juga diharapkan berfungsi sebagai penyeimbang, pembaharu, dan memberitakan kebenaran. Penelitian ini mencoba menjawab tentang netralitas berita media terkait dengan isu-isu sosial-politik. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, observasi, wawancara mendalam, dan studi pustaka. Hasil penelitian menunjukkan bahwa pemberitaan media massa tentang sosial-politik masih belum netral. Hasil penelitian juga menunjukkan bahwa pemberitaan media massa membesar-besarkan masalah, tidak memberikan solusi, dan kadang-kadang hanya memberikan sensasi saja.KATA KUNCI: Media baru, berita dan opini, komunikasi, netral, kreatif, memberikan solusi, dan perubahan baru.Â Â About the Authors: Rita Destiwati, M.Si. is a Lecturer at the Telkom Polytechnic, Jalan Telekomunikasi, Terusan Buah Batu, Bandung, West Java, Indonesia; and Junardi Harahap, M.Si. is a Lecturer at the UNPAD (Padjadjaran University), Jalan Raya Bandung-Sumedang Km.21 Jatinangor, Sumedang, West Java, Indonesia. For academic purposes, the authors can be reached at: ritadestiwati@gmail.com and junardi_harahap@unpad.ac.idHow to cite this article? Destiwati, Rita & Junardi Harahap. (2012). âToward New Media: Neutral, Creative, and Provide Solutionsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.2 [November], pp.203-214. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 17, 2012); Revised (October 19, 2012); and Published (November 20, 2012). Â  Â